2013
DOI: 10.1371/journal.pone.0073574
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Disinhibition and Sexual Risk Behavior among Adolescents and Young Adults in Malawi

Abstract: BackgroundWhile behavioral factors such as early age of sexual debut, inconsistent use of condoms and multiple sexual partners have been studied in Africa, less is known about how characteristics such as impulsivity and externalizing behaviors relate to HIV-related sexual risk-taking in that region. The purpose of this study was to develop a culturally adapted behavioral disinhibition index in a sample of adolescents and young adults in Malawi. We then sought to examine the relationship between the index and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
1
Order By: Relevance
“…Effects such as family dysfunction, divorce, alcohol, and substance use have been associated with gambling [ 11 ]. Also, similar issues have started to occur among neighbors to EAC countries, such as Malawi, where the odds ratios of alcohol and substance abuse, involvement in physical fights, theft, and vandalism were 4.17, 2.26, 3.26, and 3.96 times higher among gamblers, respectively [ 12 ]. In Uganda, evidence suggests that problem gambling is associated with mental health problems such as depression, anxiety, and suicidality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Effects such as family dysfunction, divorce, alcohol, and substance use have been associated with gambling [ 11 ]. Also, similar issues have started to occur among neighbors to EAC countries, such as Malawi, where the odds ratios of alcohol and substance abuse, involvement in physical fights, theft, and vandalism were 4.17, 2.26, 3.26, and 3.96 times higher among gamblers, respectively [ 12 ]. In Uganda, evidence suggests that problem gambling is associated with mental health problems such as depression, anxiety, and suicidality [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Present in approximately one in six preschool-aged children, behavioral inhibition is commonly regarded as one of the earliest identifiable risk factors for future internalizing symptomology [27]. Contrastingly, behavioral disinhibition is defined as a temperamental trait observed as an inability to control or inhibit impulses and behaviors that may be socially inappropriate or involve substantial risk of harm [28]. Research has consistently demonstrated associations between behavioral disinhibition with future externalizing diagnoses such as Attention Deficity/Hyperactivity Disorder, Conduct Disorder, Oppositional Defiant Disorder, and Substance Use Disorders [29].…”
Section: Risk Factors For Childhood Mental Health Difficultiesmentioning
confidence: 99%
“…Prevalence levels of gambling in study participants (i.e. having gambled at least once) ranged from 16% in Malawi [ 69 ] to 68% in South Africa [ 70 ]. In the studies that engaged with both genders, men were more prone to gamble than women and were more likely to screen positively for a gambling disorder.…”
Section: Narrative Reviewmentioning
confidence: 99%